Tribal Epistemology - Isenyo Solomon Ogaba (Universitas Negeri Makassar, 2020)
The significance of Epistemology (theory of knowledge) is well known in philosophy. Hardly do we find a philosophical system without epistemology. Almost every major philosophical system has its distinct epistemological and metaphysical theses. Accordingly, if tribal philosophy is to be counted as a major system of philosophy, it is more likely that it has its distinct epistemological and metaphysical theses. In other words, if we can have a tribal epistemology distinguished from the other epistemological systems, then, we can expect to have a tribal philosophical system distinguished from other philosophical systems. To aim at the construction of a new epistemology and new philosophy, namely, tribal epistemology is very ambitious. It demands path-breaking inquiries into both epistemology and tribal culture such that a new epistemology and, along with it, a new system of philosophy can be established. I do not claim of making any such path-breaking inquiries in this work. However, I attempt to defend the idea that there can be a tribal epistemology distinct from other epistemological systems and, hence, do defend the idea of a philosophical system that can be called a tribal system of philosophy or “tribal philosophy”. Neither tribal epistemology nor tribal philosophy has been established as a major area of investigation in philosophy. In this work, I defended the very idea of a tribal epistemology with the objective that further philosophical investigations into the tribal knowledge systems can be fruitfully carried out on a plausible strong theoretical ground.